2003
DOI: 10.1073/pnas.1131007100
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic analysis of the glycosyltransferase Fringe in Drosophila

Abstract: Fringe proteins are ␤1,3-N-acetylglucosaminyltransferases that modulate signaling through Notch receptors by modifying Olinked fucose on epidermal growth factor domains. Fringe is highly conserved, and comparison among 18 different Fringe proteins from 11 different species identifies a core set of 84 amino acids that are identical among all Fringes. Fringe is only distantly related to other glycosyltransferases, but analysis of the predicted Drosophila proteome identifies a set of four sequence motifs shared a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 38 publications
1
41
0
Order By: Relevance
“…Fly stocks were obtained from the Bloomington Stock Center and the Vienna Drosophila RNAi Center (VDRC), or alternative published sources as noted: P{EPgy2}Eaat1 EY20741 ; Df(2L)30A-C (here denoted Eaat1 Df ); UAS-mCD8::RFP; UAS-Eaat1; UAS-Pros RNAi (VDRC ID 101477); Eaat1-Gal4 (Rival et al, 2004); htl-Gal4 (Shishido et al, 1997); Repo-Gal4 (Sepp and Auld, 2003); tub-Gal80 ts (McGuire et al, 2003); UAS-N ICD (Go et al, 1998); UAS-Hairless (Maier et al, 1999); UAS-Tom (Lai et al, 2000); UAS-Eaat1::GFP (Rival et al, 2004); UAS-mCD8::GFP (Lee and Luo, 1999); UAS-nuclearGFP (van Meyel et al, 2003); Su(H)-lacZ (Griffiths et al, 2007); and fng L73 and fng 13 (Irvine and Wieschaus, 1994;Correia et al, 2003). To create CG31235-nuclear green fluorescent protein (nGFP) and CG31235-Gal4, we PCR amplified 3004 base pairs (bp) of regulatory sequences located immediately upstream of CG31235 using the primers 5Ј-CATAGTGCATTGGTGAGGTGT-3Ј and 5Ј-TACTGGGTGCGCGTTAGGTC-3Ј.…”
Section: Methodsmentioning
confidence: 99%
“…Fly stocks were obtained from the Bloomington Stock Center and the Vienna Drosophila RNAi Center (VDRC), or alternative published sources as noted: P{EPgy2}Eaat1 EY20741 ; Df(2L)30A-C (here denoted Eaat1 Df ); UAS-mCD8::RFP; UAS-Eaat1; UAS-Pros RNAi (VDRC ID 101477); Eaat1-Gal4 (Rival et al, 2004); htl-Gal4 (Shishido et al, 1997); Repo-Gal4 (Sepp and Auld, 2003); tub-Gal80 ts (McGuire et al, 2003); UAS-N ICD (Go et al, 1998); UAS-Hairless (Maier et al, 1999); UAS-Tom (Lai et al, 2000); UAS-Eaat1::GFP (Rival et al, 2004); UAS-mCD8::GFP (Lee and Luo, 1999); UAS-nuclearGFP (van Meyel et al, 2003); Su(H)-lacZ (Griffiths et al, 2007); and fng L73 and fng 13 (Irvine and Wieschaus, 1994;Correia et al, 2003). To create CG31235-nuclear green fluorescent protein (nGFP) and CG31235-Gal4, we PCR amplified 3004 base pairs (bp) of regulatory sequences located immediately upstream of CG31235 using the primers 5Ј-CATAGTGCATTGGTGAGGTGT-3Ј and 5Ј-TACTGGGTGCGCGTTAGGTC-3Ј.…”
Section: Methodsmentioning
confidence: 99%
“…The proband's parents, with normal spinal anatomy, were both heterozygous for the mutant allele. The phenylalanine residue substituted is highly conserved (Correia et al, 2003) and close to the active site of the enzyme. The mutation created a novel MseI restriction enzyme site, which was used to confirm the sequencing results in the pedigree.…”
Section: Lunatic Fringementioning
confidence: 99%
“…We also note that four of the putative core 1 GalTs (CG3119, CG2975, CG18558, and CG2983) are located in close proximity to each other on the second chromosome (Table 1), suggesting that they arose from relatively recent duplication events. By BLASTP (Correia et al, 2003) or ClustalW analysis, CG9520 is both the closest Drosophila homologue of human core 1 GalT1, and the closest homologue of most of the putative Drosophila core 1 GalTs, and thus appears to represent the ancestral core 1 GalT in Drosophila (Fig. 1).…”
Section: Core 1 Galts In Drosophilamentioning
confidence: 99%
“…However, based on bioinformatic analysis, we suggested that Drosophila are likely to encode at least eight distinct core 1 GalT domains, which at that time were annotated as seven distinct genes (CG9520, CG8708, CG2975, CG3119, CG7440, CG13904, CG18558), one of which (CG13904) encoded two tandemly repeated core 1 GalT domains (Correia et al, 2003). Another gene, CG2983, shares a high degree of overall sequence similarity with the other putative core 1 GalTs, but appears to lack critical amino acids within the most highly conserved sequence motifs (Correia et al, 2003). In a subsequent refinement of the Drosophila genome annotation, CG13904 has been split into two adjacent genes, CG34056 and CG34057 (Drysdale and Crosby, 2005).…”
Section: Core 1 Galts In Drosophilamentioning
confidence: 99%
See 1 more Smart Citation